2012
DOI: 10.1039/c2cp43362a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient SO2 absorption/activation and subsequent utilization by polyethylene glycol-functionalized Lewis basic ionic liquids

Abstract: Up to now, flue-gas desulfurization (FGD) is one of the most effective techniques to control SO(2) emission from the combustion of fossil fuels. The conventional technology for FGD poses serious inherent drawbacks such as formation of byproducts and volatilization of solvents. In this work, polyethylene glycol (PEG)-functionalized Lewis basic ionic liquids (ILs) derived from DABCO were proved to be highly efficient absorbents for FGD due to its specific features such as high thermal stability, negligible vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 65 publications
10
53
0
Order By: Relevance
“…In particular, the ILs functionalized by amine groups have exhibited a very high SO 2 adsorption capacity 1417 . The chemical interaction between SO 2 and amine groups in the ILs constructs a charge-transfer complex 18, 19 , which forms relatively unstable ionic structure that can reduce the energy requirement for SO 2 desorption 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the ILs functionalized by amine groups have exhibited a very high SO 2 adsorption capacity 1417 . The chemical interaction between SO 2 and amine groups in the ILs constructs a charge-transfer complex 18, 19 , which forms relatively unstable ionic structure that can reduce the energy requirement for SO 2 desorption 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, guanidinium 2123 , alkanol amine 24 , 1,4-Diazobicyclo[2,2,2]octane (DABCO) 20 , and azole-based ILs 2, 16, 25, 26 have been developed as chemical adsorbents for SO 2 . Even though a number of functional groups have been reported in the IL fields, practical applications have not yet been realized, because there has been a huge drawback which is relatively slow SO 2 absorption rate due to the high viscosity of the ILs 27 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PEG‐functionalized DABCO150 presents a highly reversible SO 2 absorption capability (4.38 mol per mol IL, even under 0.1 bar SO 2 ) and allows the possibility of trapping SO 2 as cyclic sulfites through the addition of a suitable epoxide and activation of this latter by a Lewis base IL (i.e., [PEG 150 Medabco]Br; Scheme ).…”
Section: Applicationsmentioning
confidence: 99%
“…In recent years, more Electronic supplementary material The online version of this article (doi:10.1007/s00894-015-2747-5) contains supplementary material, which is available to authorized users. and more researchers have reported the use of ILs to reversibly capture SO 2 and CO 2 by utilizing both physical and chemical interactions [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Very recently, Yang and Han et al [26] reported that two functionalized ILs, 1-(2-diethylaminoethyl)-3-methylimidazoliu bis (trifluoromethylsulfonyl)-imide ( A specific intermolecular interaction involving pnicogen, chalcogen and halogen atoms as acceptors of electron density, has been studied extensively in recent years [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 97%